(3RGO GdeSGaQ hZQI eMjG GdCOjH GdSGaQs - (3UahGf Hf EOQjS Hf EHQGgje GdJLjHj GdeQSqj, CHh HMQ,J (B598 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg agPg Ledg YdbJgG ef CTYGQ GdehdOjf ef COQcJg HYeQi GhdMbg Cgd YUQi hde GJhN HGdJbOje ajge hdG GdJCNjQ ETYGQkG HeRjI hdGJfbU JYUH s
(3BNQgG (B:s
(3HYV CHjGJ ai eOM GdQShd(B((3U(B) (3hYdi PcQ gPG GdeOM GdTQja bGd(B: (3jGhahO Gddg bO Je HGdefi agfjFkG dce Ggd Gdefi bO YQafG YQaGJ eYce adgPG HQM GdThb HfG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B205 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B19s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B63 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B946s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(355) s
Keywords: (3GdCOHs